Association between spatial distribution of leukocyte subsets and clinical presentation of head and neck squamous cell carcinoma - Netzer, Christoph; von Arps-Aubert, Vanessa; Mačinković, Igor; von der Grün, Jens; Küffer, Stefan; Ströbel, Philipp; von Knethen, Andreas; Weigert, Andreas; Beutner, Dirk (Frontiers in Immunology, 2024)
each other influences the likelihood of whether and how these cells interact with each other. In this study, the effect of spatial distribution on the function of leukocyte subsets in the microenvironment of human head and neck squamous cell carcinoma (HNSCC) was assessed by multiplex immunohistochemistry (IHC). Leukocyte subsets underwent further classification based on analysis of two previously published HNSCC single-cell RNA datasets and flow cytometry (FC). IHC revealed different distribution patterns as well as functional heterogeneity of leukocytes differentiated by CD68 and CD163. While CD68 hi CD163 lo and CD68 hi CD163 hi cells accumulated near the tumor sites, CD68 lo CD163 hi cells were more evenly distributed in the tumor stroma. Spatial analysis also suggests that in HNSCC PD-L1/PD-1 interactions occur predominantly near tumor sites, as PD-L1 hi and PD-1 hi cells predominantly clustered around tumor nests. High cell density of PD-L1hi CD68 hi CD163 hi cells or PD-1hi T cells in close proximity to the tumor correlated with significantly improved survival, suggesting that both spatial localization and entity of interacting cells play a critical role in whether PD-L1/PD-1 interactions positively or negatively affect survival. Flow cytometry and singlecell RNA yielded high variability within the CD68/CD163 subgroups. While the CD68 hi CD163 lo and CD68 hi CD163 hi subsets were mainly formed by macrophages (MΦ), the CD68 lo CD163 hi cells appeared to be predominantly dendritic cells (DCs).Differentiation based on CD64, CD80, CD163, and CD206 emerged that TAM in HNSCC occupy a broad spectrum within the classical M1/M2 polarization.Remarkably, the MΦ subsets expressed predominantly CD206 and little CD80, whereas the DC subsets expressed more CD80 and less CD206, supporting the hypothesis that the CD68/CD163-IHC subsets have distinct functions in the microenvironment of HNSCC. These results highlight the association between changes in spatial leukocyte distribution patterns and the development and clinical outcome of HNSCC.